1996
DOI: 10.1007/bf01692864
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorobenzoates on the utilisation of chlorobiphenyls and chlorobenzoate mixtures by chlorobiphenyl/chlorobenzoate-mineralising hybrid bacterial strains

Abstract: Chlorobenzoates (CBA) arise as intermediates during the degradation of polychlorinated biphenyls (PCBs) and some chlorinated herbicides. Since PCBs were produced as complex mixtures, a range of mono-, di-, and possibly trichloro-substituted benzoates would be formed. Chlorobenzoate degradation has been proposed to be one of the rate-limiting steps in the overall PCB-degradation process. Three hybrid bacteria constructed to have the ability to completely mineralise 2-, 3-, or 4-monochlorobiphenyl respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Effect of 3,5-diCB on 2-CB degradation by the mixed culture Several Authors have shown 3,5-diCB to have a strong inhibitory effect on the growth of different microorganisms in pure culture when the dichloroaromatic was supplied in combination with another CB as growth substrate (Baggi & Zangrossi 1995;Hernandez et al 1991;Miguez et al 1990;Stratford et al 1996). In a previous work we observed a similar effect on the growth of 2m.c.…”
Section: 5-dicbsupporting
confidence: 54%
See 3 more Smart Citations
“…Effect of 3,5-diCB on 2-CB degradation by the mixed culture Several Authors have shown 3,5-diCB to have a strong inhibitory effect on the growth of different microorganisms in pure culture when the dichloroaromatic was supplied in combination with another CB as growth substrate (Baggi & Zangrossi 1995;Hernandez et al 1991;Miguez et al 1990;Stratford et al 1996). In a previous work we observed a similar effect on the growth of 2m.c.…”
Section: 5-dicbsupporting
confidence: 54%
“…In fact we and other Authors have reported the occurrence of antagonistic effects on microbial growth when CB mixtures were supplied to CBdegrading microorganisms (Baggi & Zangrossi 1995Miguez et al 1990;Stratford et al 1996). In all cases 3,5-diCB was shown to be an inhibitory compound when present in combination with another CB as growth substrate.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…To date, the causes for growth interaction in the presence of mixed CBs have not yet been sufficiently elucidated. The formation of toxic metabolic intermediates such as chlorocatechol(s) and/or their meta-fission product(s) was hypothesized, but this has not always been demonstrated experimentally (Stratford et al, 1996). In other cases, interactions at the level of enzyme induction (Weissenfels et al, 1990, Baggi andZangrossi, 1999), the type of the carbon source utilised for growth (Hernandez et al, 1991) or competitive interferences with uptake systems or key enzymes involved in the first steps of the CB degradative process (Stringfellow and Aitken, 1985;Adriaens and Focht, 1991;Miguez et al, 1995;Corbella et al, 2001;Baggi et al, 2005), were postulated as the most important causes of the inhibitory phenomena.…”
Section: Introductionmentioning
confidence: 99%